Evaluating digital literacy of health professionals in Ethiopian health sectors: A systematic review and meta-analysis. - Alex Ayenew Chereka; Agmasie Damtew Walle; Sisay Yitayih Kassie; Adamu Ambachew Shibabaw; Fikadu Wake Butta; Addisalem Workie Demsash; Mekonnen Kenate Hunde; Abiy Tassew Dubale; Teshome Bekana; Gemeda Wakgari Kitil; Milkias Dugassa Emanu; Mathias Nega Tadesse (PLoS ONE)
Background Digital literacy refers to the capacity to critically assess digital content, use digital tools in professional settings, and operate digital devices with proficiency. The healthcare sector has rapidly digitized in the last few decades. This systematic review and meta-analysis aimed to assess the digital literacy level of health professionals in the Ethiopian health sector and identify associated factors. The study reviewed relevant literature and analyzed the data to provide a comprehensive understanding of the current state of digital literacy among health professionals in Ethiopia. Methods The study was examined by using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. Evidence was gathered from the databases of Google Scholar, Pub Med, Cochrane Library, Hinari, CINAHL, and Global Health. Consequently, five articles met the eligible criteria for inclusion. The analysis was carried out using STATA version 11. The heterogeneity was evaluated using the I2 test, while the funnel plot and Egger's regression test statistic were used to examine for potential publication bias. The pooled effect size of each trial is evaluated using a random effect model meta-analysis, which provides a 95% confidence interval. Result A total of five articles were included in this meta-analysis and the overall pooled prevalence of this study was 49.85% (95% CI: 37.22-62.47). six variables, Monthly incomes AOR = 3.89 (95% CI: 1.03-14.66), computer literacy 2.93 (95% CI: 1.27-6.74), perceived usefulness 1.68 (95% CI: 1.59-4.52), educational status 2.56 (95% CI: 1.59-4.13), attitude 2.23 (95% CI: 1.49-3.35), perceived ease of use 2.22 (95% CI: 1.52-3.23) were significantly associated with the outcome variable. Conclusion The findings of the study revealed that the overall digital literacy level among health professionals in Ethiopia was relatively low. The study highlights the importance of addressing the digital literacy gap among health professionals in Ethiopia. It suggests the need for targeted interventions, such as increasing monthly incomes, giving computer training, creating a positive attitude, and educational initiatives, to enhance digital literacy skills among health professionals. By improving digital literacy, health professionals can effectively utilize digital technologies and contribute to the advancement of healthcare services in Ethiopia.